Synthesis, characterization, and brine shrimp (artemia salina) toxicity evaluation of nanocomposites carrier phytic acid/chitosan/magnetic iron oxide nanoparticles - Asey, Monica Namizie; Che Abdullah, Che Azurahanim; Abdelmonem, Mohamed; Mohd Esa, Norhaizan; Abdul Rahman, Mohd Basyaruddin (John Wiley and Sons, 2025)
The use of polymer-coated magnetic iron oxide nanoparticles (MIONs) to deliver drugs to a specific target site is among the most efficient strategies. We have developed MIONs coated with chitosan (CS) polymer, preloaded with the phytodrug phytic acid (PTA), for drug delivery applications. To fully understand the crystalline structure and surface morphology of the prepared composite nanocarrier, it is thoroughly characterised by powder X-Ray Diffraction, Fourier transform infrared spectroscopy, thermogravimetric analyses, vibrational sample magnetometer, and transmission electron microscopy. Additionally, brine shrimp (Artemia salina) are used to assess the in vitro toxicity of phytodrug-loaded MIONs-CS nanostructures. Our studies on brine shrimp have demonstrated that both the phytodrug and nanocomposite have excellent activity. As a result, our PTA-loaded MIONs/CS nanocomposite can be recommended for real-time diagnostic CS.